Dysmenorrhea in adolescents and young adults: a review in different country - De Sanctis, Vincenzo; Soliman, Ashraf T; Elsedfy, Heba; Soliman, Nada A; Soliman, Rania; El Kholy, Mohamed (Acta Biomedica Atenei Parmensis, 2017)
Background: Dysmenorrhea is still an important public health problem which may have a negative impact on female health, social relationships, school or work activities and psychological status. Methods: The aim of this review is a better understanding of the epidemiology of dysmenorrhoea and its effect on public health. Published studies in English providing relevant information on dysmenorrhea were identified by searching PubMed, Embase and Google; restricting the population to  adolescents and young adult women and the year of publishing from 2010 to August 2015, based on the keywords ‘dysmenorrhea’, ‘adolescents’ and ‘epidemiology’. In addition, the reference lists of the selected articles were examined. Results: We found 50 studies that met our inclusion criteria. The majority were cross-sectional studies on 41,140 adolescents and young women published from 2010 onward. The prevalence of dysmenorrhea varied from 34 % (Egypt) to 94% (Oman) and the number of participants, reporting very severe pain varied from 0.9 % (Korea) to 59.8% (Bangladesh). Adolescents who missed school due to dysmenorrhoea ranged from 7.7% to 57.8% and 21.5% missed social activities. About 50% of students (53.7%-47.4%) reported a family history of dysmenorrhea. Incidence of dysmenorrhea was 0.97 times lower as age in-creased (p